Tales of Canyonlands cowboys - Negri, Richard F., 1926- (Western experience., 1997)
Before Canyonlands was a national park, before tourists discovered the wildness and wonder of the Maze and the Land of Standing Rocks, before the San Rafael Desert became a hive of mineral exploration, the lands west of the Colorado and Green Rivers to the San Rafael Swell and from the Book Cliffs and San Rafael River south to the Dirty Devil River and the Henry Mountains were pastures for the stock of hardscrabble cowboys and sheepmen. Often based in the nearby villages of Green River or Hanksville, sometimes residing on remote ranches, such as the famous Robbers Roost Ranch or the Chaffin Ranch at the mouth of the San Rafael, they spent much of their time camped out on the range with their stock. They herded both Under the Ledge, along the river south across Elaterite Basin, Ernie Country, and Waterhole Flat, and above on the flats, mesas, and head canyons running from the west. They named many of the places; opened many of the trails; were there to meet and guide the first.